Fudamentals of molecular virology - Acheson, Nicholas H. (ASM Press, 2007)
The text approaches learning about virology by presenting a set of chapters each of which covers a specific virus family, using one or two well-studied viruses as examples. Each chapter is designed to tell a story about the virus under discussion, and to portray the "personality" of that virus.